Battery Internal-Heating Method via SW Mode Switching of the Drive Inverter During Electric Vehicle Stoppage - Ryuhei Hasegawa; Keiichiro Kondo; Chikako Funayama; Akihiro Imura (IEEE Access, 2025)
The discharge voltage and capacity of lithium-ion batteries (LIBs), widely used in electric vehicles (EVs), decrease at sub-zero temperatures. To enhance the drive motor’s output, it is essential to rapidly increase the battery’s temperature before startup. One effective method for heating LIBs is the use of Joule heating. Specifically, internal heating methods utilizing alternating current (AC) are gaining attention due to their reduced likelihood of precipitate lithium. In this study, we propose an internal heating method for the battery through AC using reactive power from the existing drive system when the EV is stationary. Additionally, by switching the switching (SW) mode of the drive inverter, we aim to maximize the overall effective value of the inverter output voltage, and increase the reactive power supplied to the permanent magnet synchronous motor (PMSM). The circuit characteristics and effectiveness of the proposed method were demonstrated through both simulation and experimental verification using a downscaled model.